IMPACT OF DEBRIS FLOW INTENSITIES ON PIPELINE - HABEEB, NURSYAHIRA (Universiti Teknologi PETRONAS, 2021)
Debris flow are geological phenomena in which soil and fragmented rock rush down mountainsides with liquid masses. This phenomenon had causes negative impact on pipeline structure built at steep slope that led to pipeline failure. These had caused major large cost and less economical to the company and locals involved. Thus, this research is made to identify the condition of pipeline details and debris flow material properties that can cause highest impact on the pipeline. The pipeline modelling was simulated by using Abaqus CAE numerical modelling software by varying the wall thickness, impact pressure of debris flow and impact angle of the force. This research focuses on three impacts outcomes on pipelines: stress, strain, and displacement, in order to determine the most serious pipeline failure after those conditions are applied.